Effect of Ti and its compounds on the mechanical properties and microstructure of B4C ceramics fabricated via pressureless sintering. Issue 10 (15th May 2021) - Liu, Guanqi; Chen, Shixing; Zhao, Yanwei; Fu, Yudong; Wang, Yujin
Abstract: The addition of Ti and its compounds particles has the potential to effectively enhance the fracture toughness of B4 C ceramics. However, the influence of different Ti-based compounds on B4 C ceramics has not been extensively studied. In this work, B4 C–TiB2 multiphase ceramics were prepared by adding 5% Ti or its compounds (TiO2, TiB2 or TiC) in B4 C and the effects of the additives on the B4 C ceramics were studied. For this purpose, we adopted a sintering process carried out in situ in the absence of pressure at a temperature of 2250 °C for 1 h. It was evident from the results that the additives are capable of enhancing the sintering densification characteristics and the properties exhibited by B4 C, as opposed to single-phase B4 C ceramics. Additionally, different additives have varied effects on the microstructures and mechanical properties of B4 C–TiB2 multiphase ceramics. The results of the study indicate that the TiC-added sample exhibits the most optimal mechanical properties, with 4.52 MPa m 1/2 fracture toughness, 344.0 MPa flexural strength, 26.2 GPa hardness, and 516.0 GPa elastic modulus.